Сукцесії трав’яного покриву в пірогенно пошкоджених соснових фітоценозах лісостепової частини Харківщини - Voron, V. P.; Melnyk, Ye. Ye.; Sydorenko, S. G.; Koval, I. M.; Sydorenko , S. V. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2021)
Introduction The level of pyrogenic transformation of forest ecosystems damaged by surface fires can be determined by a differentiated assessment of their main components. After the fire, the ecological environment of plants changes in a special way. For example, even after surface fires of medium intensity, the amount of light reaching the surface under the tree canopy increases due to the death of some trees. Sunlight penetrates more into the soil, heating and drying it. The litter burning creates favorable conditions for seed germination and the emergence of self-seeding. At the same time, the ash left on the soil surface can significantly alkalize the soil, which affects many forest associations. Indirect analysis of such phenomena is possible through the use of phytoindication methods. The aim of the study was to assess the impact of surface fires on the development of grass and shrub layers in pine forests, as well as make phytoindication estimation of the studied forest phytocenoses. Materials and Methods Sample plots were established in pine forests within the Forest-Steppe part of Kharkiv region, damaged by surface fires. For the study, 23 permanent sample plots were established in middle-aged pine stands. The species composition, ecomorphic and biomorphic structures of the above-ground cover were compared for a detailed analysis of changes after surface fires. Ecological amplitudes were estimated based on the phytoindication method of ecological factors developed by Didukh with the use of unified scales for the Ukrainian flora species. The light regime and trophic properties of soils caused by fire disturbance were investigated. Results Based on the series of field geobotanical studies, 57 species of plants belonging to 23 families were identified. Among the most common species are Erigeron canadensis L. (Asteraceae), Calamagrostis epigeios L. (Poaceae), Lactuca serriola L. (Asteraceae), and Chamaecytisus ruthenicus (Fisch. Ex Wol?osz. Kl?sk.) (Fabaceae). In a case when pine stands are damaged by fires before the beginning of the growing season, i.e. in early spring, then the Erigeron canadensis L. and Calamagrostis epigeios L. may appear in a few months. Spring fire does not destroy cereal vegetation but creates conditions for the dominance of a number of adventitious and invasive species, such as Erigeron canadensis L. and Erigeron annuus L. In the second and third years after the spring fires, there is also a significant increase in the total projective cover of the above species, especially of Erigeron canadensis L. (from 22 to 52%) and Calamagrostis epigeios L. (from 11 to 46%). After summer surface fires, living ground cover in the year of fire often does not appear. Conclusions After the destruction of the ground cover by fire, forest species are almost absent in the first years. The living ground cover developed mainly through the formation of shoots from the buds of meadow species, which had survived after the fire (Calamagrostis epigeios L.), and through the self-sowing of weeds such as Lactuca serriola L. and Crepis tectorum L. and invasive species that are able to very quickly inhabit new areas, especially Erigeron canadensis L. In subsequent years (up to three years) forest species are found in minimal numbers. Only four years after the fire, a significant decrease in weeds and an increase of forest species (Festuca ovina L., Chamaerion angustifolium (L.) Holub., etc.) were observed. The number of meadow species was almost unchanged during the monitoring period. Significant changes in most environmental factors were not observed after the fires and in subsequent years in forest ecosystems. Only the light availability has increased noticeably during the first year, due to the tree canopy thinning.